2018
DOI: 10.1177/1055665618768539
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Band Syndrome: A Multidisciplinary Care Approach to the Treatment of a Rare Case

Abstract: Amniotic band syndrome (ABS) is a rare developmental disorder associated with defects such as syndactyly, facial and/or palatal clefts, and dental anomalies like malformed or impacted teeth. In this report, a patient with ABS was successfully treated with orthodontic, endodontic, and periodontal therapies. Cone beam computed tomography revealed a unique eruptive path of the impacted central incisor through the incisive canal and cleft area. The tooth was occlusally and functionally stable after 1 year of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…10 Craniofacial defects that are seen in association with ABS include Tessier clefts; hydrocephalus; encephalocele; myelomeningocele; plagiocephaly; mandibular hypoplasia; hair whorls; skin tags; forehead prominence; and supernumerary, impacted, malformed, or absent teeth. 6,11,33,[35][36][37][38] In addition, ophthalmologic deformities including telecanthus, epiphora, microphthalmos, microcornea, and colobomas have been reported. 39 Although the exact mechanism of facial clefting in association with ABS is unclear, it has been observed that facial clefts in the setting of ABS are more complex than isolated facial clefts, and can also present with translocation of upper extremity appendages into the facial cleft itself.…”
Section: Craniofacialmentioning
confidence: 99%
See 2 more Smart Citations
“…10 Craniofacial defects that are seen in association with ABS include Tessier clefts; hydrocephalus; encephalocele; myelomeningocele; plagiocephaly; mandibular hypoplasia; hair whorls; skin tags; forehead prominence; and supernumerary, impacted, malformed, or absent teeth. 6,11,33,[35][36][37][38] In addition, ophthalmologic deformities including telecanthus, epiphora, microphthalmos, microcornea, and colobomas have been reported. 39 Although the exact mechanism of facial clefting in association with ABS is unclear, it has been observed that facial clefts in the setting of ABS are more complex than isolated facial clefts, and can also present with translocation of upper extremity appendages into the facial cleft itself.…”
Section: Craniofacialmentioning
confidence: 99%
“…10 These interventions often necessitate the involvement of a multidisciplinary team of specialists for orthognathic, orthodontic, and ophthalmologic management. 6,39 Possible interventions by the pediatric plastic surgeon include cleft lip repair, cleft palate reconstruction, facial cleft closure, macrostomia repair, and mandibular distraction osteogenesis. 10,11,37…”
Section: Presentation and Management By Locationmentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic band syndrome is a rare syndrome occurring about 1,200 in 15,000 newborns [1,2] and is a major cause of congenital malformation of the fetus. In most cases, there are membranes binding the fetus's limbs, fi ngers, toes [3][4][5], and skull, including a deformation of face, mouth, nose, eyes, chest, ribs, spinal bone, front surface of sexual organs, and anal hole [6,7]. The prediction of the disease depends on the severity of the pathology caused by the organs tied with membranes causing an abortion up to 1 in 70 people [8,9].…”
Section: Introductionmentioning
confidence: 99%